Amalan Kerja-Kerja Penyelenggaraan Proses Rawatan Air oleh Pihak Ranhill SAJ - Salim, Syufian ‘Afif; Omar, Roshartini (Research in Management of Technology and Business, 2021)
Clean water supply is very important as it is a domestic consumption across the country. In the daily routine also need water no matter for our own use or the use of others. Nevertheless, in the current news many states that the water supply is always disrupted. Therefore, this study has examined the practice of maintenance work that affects the water treatment process by Ranhill SAJ, identify the problems often faced by Ranhill SAJ when the practice of water treatment process maintenance work done, and identify the steps that need to be done to reduce the problems encountered when the maintenance work of the water treatment process by Ranhill SAJ took place. The study was conducted at a Ranhill SAJ plant located in Panchor, Muar, Johor. This study used the interview method with three representatives from Ranhill SAJ, namely one person from the assistant technician and two people from the operator. Findings show that the practice of water treatment process maintenance work by Ranhill SAJ is the best if not compared to Singapore. The problems that Ranhill SAJ faced during the water treatment process maintenance work were river water pollution, too long a time, and the occurrence of natural disasters such as drought. Measures to overcome the problem are more frequent in-depth maintenance, save enough water because clean water in Malaysia is declining, and follow the instructions from superiors based on the guidelines that have been given. The importance of the study is aimed at consumers, academics, and Ranhill SAJ. This party can also find out the practice of water treatment process maintenance work by Ranhill SAJ.